Psychrobacter Pygoscelis Sp. Nov. Isolated from the Penguin Pygoscelis Papua - Cortez-San Martin, M (Microbiology Society, 2020)
One slightly beige-white pigmented, Gram-stain-negative, rod-shaped bacterium, strain I-STPP5bT, was isolated from the trachea of a Gentoo penguin chick individual (Pygoscelin papua) investigated in Fildes Bay, Chilean Antarctic (62° 12′ S, 58° 57′ W). I-STPP5bT consists of a 3.4 Mb chromosome with a DNA G+C content of 44.4 mol%. Of the 3056 predicted genes, 1206 were annotated as hypothetical proteins and 51 were tRNAs. Phylogenetic analysis based on nearly full-length 16S rRNA gene sequences showed that the isolate shared a 16S rRNA gene sequence identity to the type strains of Psychrobacter phenylpyruvicus (98.8%), Psychrobacter arenosus and Psychrobacter pasteurii (both 98.3%), Psychrobacter piechaudii (98.2%) and Psychrobacter sanguinis (98.1%), but 16S rRNA gene sequence similarities to all other Psychrobacter species were ≤98.0%. Partial gyrB nucleotide and amino acid sequence similarities among strain STPP5bT and the next related type strains were all below 81.8 and 92.9%, respectively. DNA–DNA hybridisation (DDH) with P. phenylpyruvicus LMG 5372T, P. arenosus DSM 15389T and P. sanguinis DSM 23635T also showed low values (all below 30%). The main cellular fatty acids of the strain were C18:1 ω9c and C16:1 ω7c and/or C16:1 ω6c. Based on phylogenetic, chemotaxonomic, genomic and phenotypic analyses we propose a new species of the genus Psychrobacter, with the name Psychrobacter pygoscelis sp. nov. and strain I-STPP5bT (=CIP 111410T= CCM 8799T=LMG 30301T) as type strain. © 2020 The Authors.